Glucocorticoids for Duchenne Muscular Dystrophy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2013)
Investigators at the Dubowitz Neuromuscular Centre, Great Ormond Street Hospital, and other centers in the UK, conducted a prospective longitudinal study across 17 neuromuscular centers in the UK of 360 boys aged 3-15 years with Duchenne muscular dystrophy who were treated with daily or intermittent (10 days on/10 days off) prednisolone for a mean duration of 4 years.